The Improvement of Creative Industries-Culinary SMEs in The Tourist Destinations of The Greater Bandung Region - Wardoyo, Munajat; Latif, Aqilah Nurul Khaerani (ITB Journal Publisher, LPPM ITB, 2018)
This research aims as a consideration in formulating policies, regulations, strategies, and culinary tourism feasibility studies to be sustainable. The development of culinary products as a model for culinary tourism development in Indonesia. It aims to improve the welfare of small and medium creative industries in the food and beverage sector in the Greater Bandung area. The method used is the method of evaluating community participation, FGD and experiments. Data collection techniques with direct interviews and questionnaires. The data analysis method used is the general electric matrix. The results of this study indicate several things that must be considered by SMEs in eating and drinking to support the business, namely knowledge and experience, product uniqueness, product innovation, capital, the courage to do business, clear financial statements, proposals, cooperation with supply chains, and determining prices.